2013
DOI: 10.1136/bjophthalmol-2013-303415
|View full text |Cite
|
Sign up to set email alerts
|

Small incision lenticule extraction (SMILE) and femtosecond laser LASIK: comparison of corneal wound healing and inflammation

Abstract: Aim To evaluate and compare early corneal wound healing and inflammatory responses after small incision lenticule extraction (SMILE) versus femtosecond laser laser in situ keratomileusis (LASIK). Methods Thirty-six eyes of 36 rabbits underwent SMILE, while another 36 eyes of 36 rabbits were treated with femtosecond laser LASIK. All the eyes were subjected to the same refractive correction of −6.00 DS/−1.00 DC. Twelve eyes that had no surgery were included for control. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
92
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(97 citation statements)
references
References 24 publications
3
92
0
2
Order By: Relevance
“…[48][49][50] Comparative studies of postoperative corneal healing have shown significantly fewer inflammatory cells in corneas treated with femtosecond lenticule extraction/small-incision lenticule extraction than with femtosecond laser-assisted LASIK. 51,52 In the study by Riau et al, 52 a statistically significant increase in inflammatory cells was observed when higher spherical corrections were attempted (À6.00 D to À9.00 D) with femtosecond laser-assisted LASIK than with femtosecond lenticule extraction/small-incision lenticule extraction. A greater proportion of ablated tissue during higher refractive corrections and increased energy absorption from the excimer laser were suggested as probably explanations for the differences.…”
Section: Postoperative Inflammationmentioning
confidence: 93%
“…[48][49][50] Comparative studies of postoperative corneal healing have shown significantly fewer inflammatory cells in corneas treated with femtosecond lenticule extraction/small-incision lenticule extraction than with femtosecond laser-assisted LASIK. 51,52 In the study by Riau et al, 52 a statistically significant increase in inflammatory cells was observed when higher spherical corrections were attempted (À6.00 D to À9.00 D) with femtosecond laser-assisted LASIK than with femtosecond lenticule extraction/small-incision lenticule extraction. A greater proportion of ablated tissue during higher refractive corrections and increased energy absorption from the excimer laser were suggested as probably explanations for the differences.…”
Section: Postoperative Inflammationmentioning
confidence: 93%
“…Similarly, CCT, Kf, Ks, and Km also did not regain its stability at 3 months except in corneal biomechanics. When compared with SMILE, FS-LASIK induced more keratocyte apoptosis, proliferation, and inflammation, 31 so IOP values after FS-LASIK seemed less stable, which may be a result of corneal structure variation.…”
Section: Discussionmentioning
confidence: 99%
“…The ReLEx SMILE method leads to a release of energy only during creation of the refractive lenticule and sidecut. In contrast, femto-LASIK surgery has manifold higher energy requirements needed for photoablation of the entire mass of removed stromal surface 30 . Last but not least, ReLEx SMILE saves time, because it is not necessary to transport the patient to another laser during surgery.…”
Section: Discussionmentioning
confidence: 99%